Faktor-Faktor Yang Mempengaruhi Praktik Kesehatan Reproduksi Remaja Di SMA Negeri 1 Purbalingga Kabupaten Purbalingga - Cahyo, Kusyogo; Kurniawan, Tri Prapto; Margawati, Ani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2008)
Background: Youth behavior is becoming more permissive in terms of sexual interaction. These matters generate many cases of unwanted pregnancy and abortion. This research is aimed to know the factors influencing youth reproduction health practices in SMA 1 Purbalingga, district of Purbalingga by using a cross sectional study.Method: This study applies quantitative using questionnaires for data collection from 110 samples and combines with a qualitative using in-depth interview.Results: This study revealed that respondents’ level of knowledge in term of sexual health is mostly at sufficient level. The attitude of respondents is mostly still traditional and supported to have sexual practices such as abstinence. Most respondents admitted that their parents have no skill to inform them about reproductive issues. So they prefer to access informationfrom friends and media. Bivariate analysis shows that knowledge, parent’s role and media have significantly correlated with youth reproductive health practices. However respondent attitude and teacher’s role factors have no correlation with reproductive health practices.Keywords: reproductive health, practice, youth.